Quasi one-dimensional organic conductors: from Fröhlich conductivity and Peierls insulating state to magnetically-mediated superconductivity, a retrospective - Jerome, Denis; Bourbonnais, Claude (Comptes Rendus. Physique)
It is indisputable that the search for high-temperature superconductivity has stimulated the work on low-dimensional organic conductors at its beginning. Since the discovery of true metal-like conduction in molecular compounds more than 50 years ago, it appeared that the chemical composition and the quasi one-dimensional crystalline structure of these conductors were determining factors for their physical properties; materials with incommensurate conduction band filling favoring the low-dimensional electron-phonon diverging channel and the establishment of the Peierls superstructure and more rarely superconductivity at low temperature, while those with commensurate band filling favor either magnetic insulating or superconducting states depending on the intensity of the coupling between conductive chains. In addition, the simple structures of these materials have allowed the development of theoretical models in close cooperation with almost all experimental findings.Even though these materials have not yet given rise to true high-temperature superconductivity, the wealth of their physical properties makes them systems of choice in the field of condensed matter physics due to their original properties and their educational qualities. Research efforts continue in this field. The present retrospective, which does not attempt to be an exhaustive review of the field, provides a set of experimental findings alluding to the theoretical development while a forthcoming article will address in more details the theoretical aspect of low dimensional conductors and superconductors.